Membangun Rasa Kedamaian Sebagai Cara Untuk Menghindari Konflik Ditengah-Tengah Masyarakat Desa Bahalbatu III - Harjaya Situmeang (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
conflict is something that often occurs in the midst of people's lives. Including in Bahalbatu III Village, conflict also often occurs in various individuals, groups, and conflicts also occur between countries. Conflict can have both negative and positive impacts on society. Based on this journal and also in accordance with incidents that have been observed, that conflicts between individuals and groups occur very often, which is why it is important to build a sense of peace, a sense of mutual respect for each other as a model to avoid conflict or disputes in the midst of society.